RADIOSCAPHOLUNATE (RSL) FUSION ON SECONDARY OA WRIST WITH NEGLECTED DISLOCATION RADIOCARPAL JOINT AND CONTRACTURE DUE TO ENTRAPMENT OF SUPERFICIAL FLEXOR TENDON INDEX FINGER OF LEFT HAND - Rian, Rahmad; Hadinoto, Seti Aji; Sumarwoto, Tito; Utomo, Pamudji; Tulandi, M qathar RF Tulandi (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2021)
ABSTRACT Background: When pain, deformity and instability compromise wrist function, wrist stabilization by means of fusion is a procedure of recognized validity. The goal of wrist arthrodesis is to provide the patient with a stable wrist for power grip and the predictable relief of pain while sacrificing wrist motion. The radioscapholunate (RSL) fusion is one of salvage procedure indicated in the case of traumatic or degenerative osteoarthritis of the radiocarpal joint, involving the lunate facet of the radius. RSL-fusion reduced total wrist motion (3 MC/Rad) in the F/E axis to an average of 49% of F/E in the unfused wrist but preserves midcarpal joint motion while alleviating pain. Case Report: We report a 43-year-old male patient with pain on his left wrist. 10 months before admission, he felt down from stairs with his left hand bear his body weight. He broke his wrist and got surgery at that time. Because still feel pain and his index finger can’t fully extensed, he brought to Soeharso orthopaedic hospital. Here, we have done RSL-fusion using cross pinning K-Wire to reduce pain, distal scapoid excision to optimizing radial angulation and release superficial flexor tendon index finger of left hand. Discussion: With Secondary OA of left wrist post traumatic with neglected radiocarpal dislocation and superficial flexor tendon contracture due to entrapment index finger of left hand post RSL-fusion, distal scapoid excision and release contracture can reduce pain at radiocarpal joint and improve range of movement. Conclusion: The goal of Radioscapholunate (RSL) fusion is to optimizing wrist motion and strength while minimizing or eliminating pain Keywords: Radioscapholunate fusion, partial wrist arthrodesis, limited wrist fusion, reduce pain